Digital Marketing and Market Competitiveness of MSME, Cottage, and Rural Industry Products in Gujarat (London Journal of Engineering Research, 2026)
Digital marketing is increasingly shaping the competitiveness of Micro, Small and Medium Enterprises (MSMEs), cottage industries, and rural product enterprises by improving visibility, reducing intermediary dependence, widening customer reach, and enabling product differentiation. This paper develops an IEEE-style conceptual and policy-grounded study focused on Gujarat, a state with strong MSME depth and a distinctive ecosystem of handloom, handicraft, khadi, agro-processing, and village products. The paper combines official policy context, current national MSME dashboard statistics, digital commerce inclusion logic, and a field-oriented research design to examine how social media, messaging commerce, online catalogues, and e-marketplaces influence competitiveness outcomes. The proposed model links digital marketing adoption with market access, customer trust, conversion, sales growth, and margin improvement, while recognizing moderating constraints such as digital literacy, logistics, packaging, language, and payment confidence. The paper concludes that digital marketing should be treated not merely as a promotion channel but as a competitiveness infrastructure for Gujarat’s MSME and rural product economy.